The miracle planet - Yahya, Harun, 1956-; Okur Production (Turkey : Okur Production, 2000)
This film discovered about amazing planet called earth and the universe.
vol.1. The miracle planet -1.- vol.2. The design in light and water
Keywords: Islam and science; Cosmology; Creation (Islam)